Neuroplasticity and the next wave of antidepressant strategies - Hayley, Shawn; Litteljohn, Darcy (Frontiers in Cellular Neuroscience, 2013)
Depression is a common chronic psychiatric disorder that is also often co-morbid with numerous neurological and immune diseases. Accumulating evidence indicates that disturbances of neuroplasticity occur with depression, including reductions of hippocampal neurogenesis and cortical synaptogenesis. Improper trophic support stemming from stressor-induced reductions of growth factors, most notably brain derived neurotrophic factor (BDNF), likely drives such aberrant neuroplasticity. We posit that psychological and immune stressors can interact upon a vulnerable genetic background to promote depression by disturbing BDNF and neuroplastic processes. Furthermore, the chronic and commonly relapsing nature of depression is suggested to stem from “faulty wiring” of emotional circuits driven by neuroplastic aberrations. The present review considers depression in such terms and attempts to integrate the available evidence indicating that the efficacy of current and “next wave” antidepressant treatments, whether used alone or in combination, is at least partially tied to their ability to modulate neuroplasticity. We particularly focus on the NMDA antagonist, ketamine, which already has well documented rapid antidepressant effects, and the trophic cytokine, erythropoietin, which we propose as a potential adjunctive antidepressant agent.